Barriers to Self-Reporting Patient Safety Incidents by Paramedics: A Mixed Methods Study. (2nd November 2018) - Sinclair, Julie E.; Austin, Michael A.; Bourque, Christopher; Kortko, Jennifer; Maloney, Justin; Dionne, Richard; Reed, Andrew; Price, Penny; Calder, Lisa A.
Abstract: Background : A minimal amount of research exists examining the extent to which patient safety events occur within paramedicine and even fewer studies investigating patient safety systems for self-reporting by paramedics. The purpose of this study was to identify barriers to paramedic self-reporting of patient safety incidents (PSIs).Methods : We randomly distributed paper-based surveys among 1, 153 paramedics in an Ontario region in Canada. The survey described one of 5 different PSI clinical scenarios (near miss, adverse event, and minor, major or critical patient care variances) and listed 18 potential barriers to self-reporting PSIs as statements presented for rating on a 5-point Likert scale (very significant = 1 – very insignificant = 5). We invited comments on PSI self-reporting with 2 open-ended questions. We analyzed data with descriptive statistics, chi-square tests and Kruskal-Wallis H test. We used an inductive approach to qualitatively analyze emerging themes.Results : We received responses from 1, 133 paramedics (98.3%). Almost one third (28.4%) were Advanced Care Paramedics and 45.1% had >10 years' experience. The top 5 barriers to PSI self-reporting (very significant or significant, %) were the fear of being: punished (81.4%), suspended (79.6%), terminated (79.1%), investigated by Ministry of Health and Long-Term Care (78.4%), and decertified (78.0%). Overall, 64.1% responded they would self-report a given PSI. Intention to self-report a PSI varied according to scenario (22.8% near miss, 46.6% adverse event, 74.4% minor, 92.6% major, 95.6% critical). No association was found between level of training (p = 0.55) or years of experience (p = 0.10) and intention to self-report a PSI. Seven themes to improve PSI self-reporting by paramedics emerged from the qualitative data.Conclusions : A high proportion of fear-based barriers to self-reporting of PSIs exist among this study population. This suggests that a culture change is needed to facilitate the identification of future patient safety threats.